Addition of black pepper extract as an antibacterial in the manufacture of polyvinyl alcohol (PVA) and carboxymethyl cellulose (CMC) based hydrogel wound dressings - Yani, Septi Nanda; Hadiah, Fitri; Sari, Tuti Indah (Science Midwifery, 2025)
This study aims to determine the effect of adding black pepper (Piper nigrum L.) extract on the characteristics of a hydrogel wound dressing made from a mixture of Polyvinyl Alcohol (PVA) and Carboxymethyl Cellulose (CMC), and citric acid as a crosslinking agent. The manufacturing process was carried out by chemical crosslinking with varying concentrations of CMC (5%, 7.5%, 10% w/v) and black pepper extract (0%, 10%, 20%, 30%, 40% v/v). The analysis included FTIR, SEM, swelling degree, water solubility, tensile strength, and antibacterial activity against Staphylococcus aureus. The results showed that the addition of black pepper extract increased antibacterial activity and water absorption (swelling) up to 200–500%, in accordance with the standards for good wound dressings. However, increasing the concentration of black pepper extract tended to decrease water solubility due to its hydrophobic nature. Overall, the PVA/CMC hydrogel with the addition of black pepper extract showed potential as a biocompatible wound dressing with good mechanical properties and antibacterial activity. The gel released 23.12µg/cm²curcumin within 150 minutes.